Which of these equations have no solution? Check all that apply. 2(x + 2) + 2 = 2(x + 3) + 1 2x + 3(x + 5) = 5(x – 3) 4(x + 3) = x + 12 4 – (2x + 5) = (–4x – 2) 5(x + 4) – x = 4(x + 5) – 1

Respuesta :

Answer:

  • 2(x + 2) + 2 = 2(x + 3) + 1
  • 2x + 3(x + 5) = 5(x – 3)
  • 5(x + 4) – x = 4(x + 5) – 1

Step-by-step explanation:

It can be easier to see the answer if you subtract the right side of the equation from both sides, then simplify.

1. 2(x + 2) + 2 = 2(x + 3) + 1

  2(x + 2) + 2 - (2(x + 3) + 1) = 0

  2x +4 +2 -2x -6 -1 = 0

  -1 = 0 . . . . no solution

__

2. 2x + 3(x + 5) = 5(x – 3)

  2x + 3(x + 5) - 5(x – 3) = 0

  2x +3x +15 -5x +15 = 0

  30 = 0 . . . . no solution

__

3. 4(x + 3) = x + 12

  4(x + 3) - (x + 12) = 0

  4x +12 -x -12 = 0

  3x = 0 . . . . one solution, x=0

__

4. 4 – (2x + 5) = (–4x – 2)

  4 – (2x + 5) - (–4x – 2) = 0

  4 -2x -5 +4x +2 = 0

  2x +1 = 0 . . . . one solution, x=-1/2

__

5. 5(x + 4) – x = 4(x + 5) – 1

  5(x + 4) – x - (4(x + 5) – 1) = 0

  5x +20 -x -4x -20 +1 = 0

  1 = 0 . . . . no solution

Answer:

The answer is a,b and e.

Step-by-step explanation:

a. 2(x + 2) + 2 = 2(x + 3) + 1

b. 2x + 3(x + 5) = 5(x – 3)

e. 5(x + 4) – x = 4(x + 5) – 1

i just did this question on my test hope that helps ;) !